Physiologic Course of Female Reproductive Function: A Molecular Look into the Prologue of Life - Joselyn Rojas; Mervin Chávez-Castillo; Luis Carlos Olivar; María Calvo; José Mejías; Milagros Rojas; Jessenia Morillo; Valmore Bermúdez (Journal of Pregnancy)
The genetic, endocrine, and metabolic mechanisms underlying female reproduction are numerous and sophisticated, displaying complex functional evolution throughout a woman’s lifetime. This vital course may be systematized in three subsequent stages: prenatal development of ovaries and germ cells up until in utero arrest of follicular growth and the ensuing interim suspension of gonadal function; onset of reproductive maturity through puberty, with reinitiation of both gonadal and adrenal activity; and adult functionality of the ovarian cycle which permits ovulation, a key event in female fertility, and dictates concurrent modifications in the endometrium and other ovarian hormone-sensitive tissues. Indeed, the ultimate goal of this physiologic progression is to achieve ovulation and offer an adequate environment for the installation of gestation, the consummation of female fertility. Strict regulation of these processes is important, as disruptions at any point in this evolution may equate a myriad of endocrine-metabolic disturbances for women and adverse consequences on offspring both during pregnancy and postpartum. This review offers a summary of pivotal aspects concerning the physiologic course of female reproductive function.